The arachidonic acid metabolome serves as a conserved regulator of cholesterol metabolism - Demetz, E.; Schroll, A.; Auer, K.; Heim, C.; Patsch, J.; Eller, P.; Theurl, M.; Theurl, I.; Theurl, M.; Seifert, M.; Lener, D.; Stanzl, U.; et al. (2014)
© 2014 The Authors. Cholesterol metabolism is closely interrelated with cardiovascular disease in humans. Dietary supplementation with omega-6 polyunsaturated fatty acids including arachidonic acid (AA) was shown to favorably affect plasma LDL-C and HDL-C. However, the underlying mechanisms are poorly understood. By combining data from a GWAS screening in > 100,000 individuals of European ancestry, mediator lipidomics, and functional validation studies in mice, we identify the AA metabolome as an important regulator of cholesterol homeostasis. Pharmacological modulation of AA metabolism by aspirin induced hepatic generation of leukotrienes (LTs) and lipoxins (LXs), thereby increasing hepatic expression of the bile salt export pump Abcb11. Induction of Abcb11 translated in enhanced reverse cholesterol transport, one key function of HDL. Further characterization of the bioactive AA-derivatives identified LX mimetics to lower plasma LDL-C. Our results define the AA metabolome as conserved regulator of cholesterol metabolism, and identify AA derivatives as promising therapeutics to treat cardiovascular disease in humans. Omega-6 polyunsaturated fatty acids, including arachidonic acid (AA), have beneficial cardiovascular effects. Demetz et al. show that Alox5, a key enzyme of the AA pathway, regulates cholesterol in humans. Modulation of the AA pathways genetically or pharmacologically, with aspirin or bioactive AA-mimetics influences cholesterol metabolism including reverse cholesterol transport.